KEMAMPUAN TANAMAN Shorea leprosula DALAM MENYERAP CO2 DI PT SUKA JAYA MAKMUR KABUPATEN KETAPANG - Yuliana, Syarifah; Hardiansyah, Gusti; Widhanarto, Ganjar Oki (JURNAL HUTAN LESTARI, 2014)
This study aims to look at the content and potential of biomass and carbon stored in forest stumpage meranti, to see the potential of meranti wood plant stand to absorb CO2 from the atmosphere, and to develop allometric equations of potential biomass, carbon stocks and sequestration of CO2 by growth dimensions (diameter) for the relationship between the diameter of the potential of biomass, the relationship between the diameter of the carbon potential, and the relationship between the diameter of the CO2 sequestration potential .. The results showed that the potential of tree biomass (kg / ha) on the plant Shorea leprosula based on 1,2,3,4,5,6,7 and 8 age classes ranging from 1787.39 to 16.74 gr. While the carbon potential crop trees Shorea leprosula ranged from 1046.13 to 10.88 kg. Potential plant Shorea leprosula 1,2,3,4,5,6,7 and 8 year old to absorb CO2 (kg / tonne) from the atmosphere ranges from 4243.7 to 58.97 kg. Allometric equations that manggambarkan-diameter tree biomass relationship is Y = 63.180 D1, 680. Allometric equations that manggambarkan-carbon tree diameter relationship is Y = 33.627 D1, 683. Allometric equations that manggambarkan-diameter relationship of CO2 absorption is Y = 123.394 D1, 687. Key words : biomass, carbon, meranti,diameter